Access to Immunological Markers for the Management of Rheùmatoid Arthritis in Togo with Regard to 2010 ACRj EULAR Classification..... - Knlou, Malewe; BIGOT, KOFFI ANDRÉ; Kakpovi, Kodjo; Amenyah-Ehlan, Amivi; Salou, Mounerou; Mijiyawa, Moustafa; Prine-David, Mireille (My University, 2017)
Background: The American CoIlege of Rheumatology (ACR) and the European Volume 5 Issue 7 - 2017 League Against Rheumatism (EULAR) jointlY.i!efined new criteria for rheumatoid arthritis (RA) in 2010. This classification has made several changes to Malewe Knloll'*, Andre Bigot',Kodjo immunological markers. Kalqwvi', Amivi Atllpnyah-Ehlan 1 , Mouneroll Salou l Objective: To determine access to rheumatoid factors (RF), antibodies against , Moustaf.l Mijiyawa' and cyclic citruIlinated peptide (anti-CCP), erythrocyte sedimentation rate (ESR) and Mil-eille PrinC('-David 1 C-reactive protein (CRP) inrheumatology field in Togo. lDepartment ofImmunology and Molecular Biology, University ofÙJme. Togo Materials and methods: This is a cross-sectional study including patients with 'National Agencyfor Blood Transfusion (Ministry ofHealth), RA and foIlow-up between 1990 and 2016. Patient records were used to collect Benin 3Department ofRheumatology, University Hospital Sylvanus Olympia. Togo data, especially age at diagnosis, sex, date of diagnosis, ESR, CRP, RF and antiCCP. These data were entered and analyzed using Epidata and Epi-lnfo7. Patients whose diagnosis was made between 1990 and 2010 were distinguished from those diagnosed between 2011 and 2016. '(olTe,polllhng ,1lIIhor: Malewe Kolou. Department of fmmunology and MoJecular Biology, University of Lome, Results: Out of the 125 patients included in this study, 57.6% were diagnosed Togo, Tel: +228 90106600; Email: koloumalewe@hotmail.fr between 1990 and 2010. The mean age at diagnosis was 44.5 ± 14.7 years. Women represented 88% of the patients corresponding to a sex-ratio F:M of 7.3:1. ESR Recelved: September 21. 2017 : Published: Dctober 13. was available in aIl patients and increased in 92% ofthem. The mean ESR was 71 2017 ± 33.9 mm. CRP was available only in 7 (5.6%) patients and was elevated in four of them. The RF was performed in 10 (8%) patients and was positive in four of them. Anti-CCP were performed only in six (4.8%) patients and were present in only one patient. Compared to patients diagnosed between 1990 and 2010, access to CRP, RF and anti-CCP has not been improved in our patients after 2010. Conclusion: Apart from the ESR, access to other immunological markers of 2010 ACR/EULAR criteria is very low. This is responsible for delay of diagnosis and treatment of RA in Togo. l'':eywon.ls: Rheumatoid arthritis; Erythrocyte sedimentation rate; C-Reactive Protein; Rheumatoid Factor; Antibodies against cyclic citrullinated peptide
Keywords: Rheumatoid arthritis; Erythrocyte sedimentation rate; C-Reactive; Protein; Rheumatoid Factor; Antibodies against cyclic citrullinated peptide